Strategi Humas dalam Meningkatkan Dakwah Diera Perkembangan Teknologi - Efendi, Erwan; Marisa, Marisa; Dayati, Eni; Al Fatih, Siti Karmela; Setiawan, Dimas (Peneliti.net, 2024)
Da'wah is one of the important pillars of the Islamic religion. Da'wah aims to convey Islamic teachings to the wider community. In the era of technological development, da'wah faces new challenges, namely how to convey Islamic teachings effectively and efficiently by utilizing technology. This research aims to analyze public relations strategies in increasing da'wah in the era of technological development. The research results show that public relations strategies in increasing da'wah in the era of technological development include: 1) Internal strategy: creating a conducive working atmosphere for preachers, improving the quality of preachers, and building good relationships with partners. 2) External strategy: utilizing social media, building social networks, and carrying out digital da'wah campaigns. In conclusion, public relations has an important role in increasing da'wah in the era of technological development. Public relations can utilize technology to convey Islamic teachings effectively and efficiently